Electronic properties of phases in the quasi-binary Bi2Se3–Bi2S3 system. Issue 9 (3rd March 2021) - Benher, Zipporah Rini; Gardonio, Sandra; Fanetti, Mattia; Moras, Paolo; Kundu, Asish K.; Bigi, Chiara; Valant, Matjaz
Abstract : We investigated the quasi-binary Bi2 Se3 –Bi2 S3 system and experimentally demonstrated the compositional range of existence of the topological surface states. Abstract : We explored the properties of the quasi-binary Bi2 Se3 –Bi2 S3 system over a wide compositional range. X-ray diffraction analysis demonstrates that rhombohedral crystals can be synthesized within the solid solution interval 0–22 mol% Bi2 S3, while at 33 mol% Bi2 S3 only orthorhombic crystals are obtained. Core level photoemission spectroscopy reveals the presence of Bi 3+, Se 2− and S 2− species and the absence of metallic species, thus indicating that S incorporation into Bi2 Se3 proceeds prevalently through the substitution of Se with S. Spin- and angle-resolved photoemission spectroscopy shows that topological surface states develop on the surfaces of the Bi2 Se3− y S y ( y ≤0.66) rhombohedral crystals, in close analogy with the prototypical case of Bi2 Se3, while the orthorhombic crystals with higher S content turn out to be trivial semiconductors. Our results connect unambiguously the phase diagram and electronic properties of the Bi2 Se3 –Bi2 S3 system.